A study of the mechanical properties of the NEPE binders by molecular dynamic simulations and experiments. Issue 25 (1st June 2022) - Shi, La; Ren, Li; Li, Yang; Fu, Xiaolong; Meng, Saiqin; Wang, Jiangning
Abstract : The mechanical properties of NEPE binders were performed well with combining simulations and experiments. Abstract : In this study, the crosslinking structures of nitrate ester plasticized polyether (NEPE) binders were constructed by a computational procedure. Based on the final crosslinking models, the glass transition temperatures, mechanical properties, and thermal expansion coefficients of polyethylene glycol400/multi-functional isocyanate (PEG400/N-100), polyethylene glycol400/toluene diisocyanate (PEG400/HDI), polyethylene glycol400/hexamethylene diisocyanate (PEG400/TDI) and polyethylene glycol400/isophorone diisocyanate (PEG400/IPDI) models were simulated by molecular dynamics, and could be confirmed by experiments. Then the bond-length distributions, conformation properties and cohesive energy densities were used to analyze in detail how the different cured structures influenced the mechanical and thermal properties. Furthermore, the radial distribution function, mean square radius of gyration, volume shrinkage and fraction free volume were calculated, which could directly explain the relationships between the intermolecular chains and macroscopical properties of the NEPE binders. Lastly, PEG400/N-100 and PEG400/HDI systems were chosen for the experiments. The dynamic mechanical analysis results explained that PEG400-HDI showed better flexibility and its T g value was 45 °C lower than that of PEG400-N100. The mechanical properties illustrated that the ultimate tensile strength and Young's modulus of PEG400/N-100 were both to an extent higher than that of PEG400/HDI in the temperature range of −40 °C to 50 °C, according to the results provided by a universal tensile test machine. The experimental results were in good agreement with the simulation analysis. This work can help us to have an efficient comprehension on the crosslinking structures and micro-property relationships of the NEPE binders and act as a guidance for designing applicable polyurethanes in propellant applications.